2014
DOI: 10.1590/s0100-67622014000200005
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento de Dalbergia nigra (Vell.) Allemão ex Benth sob diferentes doses de cálcio, magnésio e enxofre

Abstract: O jacarandá (Dalbergia nigra (Vell.) Allemão ex Benth) é uma espécie da família Leguminosae-Fabaceae, com potencial para diversos usos, incluindo recuperação de áreas degradadas. Neste trabalho, objetivou-se verificar o crescimento das mudas de jacarandá-da-bahia sob diferentes doses dos nutrientes cálcio, magnésio e enxofre, em solos com características diferentes. O experimento foi conduzido em casa de vegetação no período de fevereiro de 2006 a junho de 2006. Os tratamentos foram delimitados segundo uma mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
0
1
1
5
Order By: Relevance
“…Therefore, limestone doses aiming to reach base saturation of 53.8% for D. nigra (which is equivalent to 735 kilos of limestone per hectare in the soil) obtained seedlings with better quality indexes. In this study, ideal V (%) results were found between 48 and 54, which are different from those found by Bernardino et al (2007) and Gonçalves et al (2014), who found no response to liming of D. nigra in dystrophic Latosol, leading them to conclude that there is no need for liming for this species under these conditions. The explanation for this fact is possibly in the genetic material of origin, which in the case of this study came from a park and a reserve where there is greater conservation/genetic variability.…”
Section: Growthcontrasting
confidence: 99%
“…Therefore, limestone doses aiming to reach base saturation of 53.8% for D. nigra (which is equivalent to 735 kilos of limestone per hectare in the soil) obtained seedlings with better quality indexes. In this study, ideal V (%) results were found between 48 and 54, which are different from those found by Bernardino et al (2007) and Gonçalves et al (2014), who found no response to liming of D. nigra in dystrophic Latosol, leading them to conclude that there is no need for liming for this species under these conditions. The explanation for this fact is possibly in the genetic material of origin, which in the case of this study came from a park and a reserve where there is greater conservation/genetic variability.…”
Section: Growthcontrasting
confidence: 99%
“…A presença do enxofre na fonte de N sulfato de amônio não influencia o crescimento das mudas de ipê-amarelo, pois já foi verificado que em espécies nativas como jacarandá-da-Bahia (Gonçalves et al, 2014) e canafístula (Cruz et al, 2012) esse nutriente é pouco requerido na fase de formação das mudas.…”
Section: Resultsunclassified
“…Para as características quantitativas (H, DC, PMSPA, PMSR e PMST), foi determinada a dose crítica de N, que é a dosagem na qual se obtém 90% da produção máxima (Gonçalves et al, 2014). Nas relações obtidas (RHDC, RHPMSPA, RPMSPAR e IQD), calculou-se a dose de N na qual o índice máximo foi atingido.…”
Section: Introductionunclassified
“…Da mesma forma, o plantio dessas espécies para fins comerciais de seus produtos madeireiros e não madeireiros estão, cada vez mais, tornando-se em uma alternativa financeira interessante (GONÇALVES et al, 2014).…”
Section: Introductionunclassified